Use of Saccharomyces cerevisiae immobilized in agarose gel as a binding agent for diffusive gradients in thin films - Menegario, Amauri A. [UNESP]; Tonello, Paulo S. [UNESP]; Durrant, Steven F. [UNESP] (Elsevier B.V., 2010)
A new binding agent, consisting of the yeast Saccharomyces cerevisiae immobilized in agarose, is proposed for use in diffusive gradients in thin films (DGT). Different gel compositions, containing from 4.5% to 20% (m/v) of S. cerevisiae and 1.5-5.0% (m/v) of agarose, were prepared and tested for uptake of Cd(II). For gels containing 20% (m/v) of S. cerevisiae, a mass of 14,900 ng has been attributed as the uptake limit of Cd for each disk. Determination of the Cd retained in the binding agent was readily carried out using a slurry of the agarose-yeast disk introduced directly into the inductively coupled plasma optical emission spectrometer. The performance characteristics of the DGT samplers, which were assembled with the proposed binding agent (25 mm disk containing 20% of S. cerevisiae and 1.5% of agarose) and a diffusive layer of cellulose (chromatographic paper 3MM Chr of 25 mm diameter), were evaluated by measuring the Cd(II) uptake at various pH values and ionic strengths. Very consistent results were found within the pH range 4.5-7.5 and at ionic strengths >= 0.005 mol L(-1). The precision of DGT measurements was characterized by relative standard deviations of <8%. No changes in the uptake of Cd(II) were observed in the samplers that were assembled with recently prepared disks or 35-day-old stored disks. The proposed material has been applied to the analyses of river and sea water samples. For determination of Cd(II), excellent agreement between the results obtained from devices assembled with the proposed material and those assembled with conventional material (Chelex-100 resin) were obtained, strongly validating the use of the agarose-yeast gel disk as a new binding agent for DGT. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Passive sampler; Diffusive gradients in thin films; Baker's yeast; Bioavailable; Cadmium